THE EFFECT OF ORGANIZATIONAL CULTURE, WORK EXPERIENCE, AND MOTIVATION ON EMPLOYEE PERFORMANCE OF PT TIGA SERANGKAI - Effendi, Charolin Gradia; Muhammad, Mahathir; Anggarini, Defia Riski (Universitas Nusa Cendana, 2025)
This study aims to analyze the effect of organizational culture, work experience, and motivation on employee performance of PT Tiga Serangkai. The research employs a quantitative approach using a survey method. The respondents consist of employees from various departments within PT Tiga Serangkai who were selected through a purposive sampling technique. Data were collected through structured questionnaires and analyzed using multiple linear regression analysis. The results of the partial test indicate that organizational culture, work experience, and motivation each have a positive and significant effect on employee performance. Furthermore, the simultaneous test confirms that these three variables collectively influence employee performance significantly. These findings highlight the importance of fostering a supportive organizational culture, enhancing employee experience, and maintaining high motivation levels to improve overall performance within the company. Keywords: Organizational Culture; Work Experience; Motivation ; Employee Performance